Injuries in agriculture – injury severity and mortality (Swiss Medical Weekly, 2013)
PRINCIPALS: Accidents in agriculture are a problem of global importance. The hazards of working in agriculture are manifold (machines, animals, heights). We therefore assessed injury severity and mortality from accidents in farming. METHODS: We retrospectively analysed all farming accidents treated over a 12-year period in the emergency department (ED) of our level I trauma centre. RESULTS: Out of 815 patients 96.3% were male and 3.7% female (p